Dor e fatores associados em adultos em trabalho remoto no contexto da pandemia da COVID-19 no Brasil - Silvestre, Brenda Alves (Universidade Federal de São Carlos, 2022)
Teleworking was a broadly encouraged measure during the COVID-19 pandemic to decrease virus dissemination, however, it is necessary to understand the impact that this type of work has been causing on these workers in terms of pain and associated factors. It is of great importance to establish a general Brazilian panorama regarding chronic pain, anxiety and sleep in workers who have had their routines changed to remote work. Objective: Identify the prevalence of chronic pain and analyze its correlation with anxiety, sleeping disorders and remote working characteristics during the COVID-19 pandemic in Brazil. Method: This is a cross-sectional study, descriptive, observational, with quantitative focus. Inclusion criteria: adults with 18 years old or above, that were working at home (remotely) full or partial time during the COVID-19 pandemic in Brazil. Exclusion Criteria: subjects with diagnosis of fibromyalgia, rheumatoid arthritis, cancer and healthcare professionals that were working on the frontline against COVID-19. Data were collected from February 2021 to January 2022. Participants were invited through social media disclosure, universities and companies, to take part in the on-line research with national coverage. Instruments: questionnaire to categorize the sample regarding socioeconomics data, health and life habits; questionnaire to evaluate pain regarding, presence, location, intensity and time under pain; the Pittsburgh Sleep Quality Index (PSQI) and General Anxiety Disorder questionnaire (GAD-7) to evaluate anxiety symptoms. Results: 328 people took part with a predominance of females (55,2%), with a mean age of 32,96 (SD=8) years and 86,3% had completed higher education. The prevalence of chronic pain was 47,9% (95% CI:42,46%;53,27%), body regions most affected by pain were lumbar spine (62,4%), cervical spine (47,1%) and head (42%) and the perceived pain was of moderate intensity (5,8, SD=2). 59,8% were working full-time remotely and 22,5% were working part-time remotely. Of the 157 people with chronic pain, 53,5% felt pain before the pandemic and continue to feel it during the pandemic, while 46,49% started to have chronic pain after the beginning of the pandemic. From subjects with chronic pain, 53,5% reported symptoms of anxiety disorders and 29,9% sleep disorders. Pain was associated with the presence of anxiety disorder symptoms (p<0,01), the presence of sleep disorders (p<0,01) and time while seated down. Conclusion: The prevalence of chronic pain in the studied population that performs remote work is high and of moderate intensity, in addition pain is associated with anxiety, sleep disorders and time in seated position.
Pain and associated factors in adults in remote work in the context of the COVID-19 pandemic in Brazil
Keywords: Dor crônica; Distúrbios do sono; Ansiedade; Pandemias; COVID-19; Teletrabalho; Chronic pain; Sleep disorders; Anxiety; Pandemics; COVID-19; Teleworking; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA